Relationship between blood heavy metals and female stress urinary incontinence from NHANES 2013–2018 - Yan-zhen Wu; Xi-meng Chen (Environmental Health and Preventive Medicine)
Background: Research has demonstrated that heavy metals and cholesterol are associated with stress urinary incontinence (SUI) in women and that heavy metal exposure can cause dyslipidemia in humans. However, the potential mediating role of cholesterol in the relationship between heavy metals and female SUI remains unexplored. Methods: The study utilized data from the National Health and Nutrition Examination Survey database from 2013–2018. Blood lead (Pb), cadmium (Cd), total mercury (Hg), manganese (Mn), selenium (Se), and methyl mercury (MeHg) were included in the study. The single and combined effects of the six metals exposure on SUI were examined using logistic analysis, restricted cubic spline (RCS) curves, weighted quantile sum (WQS) regression, and bayesian kernel machine regression (BKMR). The mediating effects of total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) were investigated through mediation analysis. Results: The study included 2241 females, with 42.66% experiencing SUI. Initial analysis of six heavy metals revealed the associations between MeHg, Pb, Cd, total Hg, and SUI (all P < 0.05). WQS regression identified that Cd, Se, and Pb were major contributors to the mixed effect causing SUI. BKMR results indicated a positive mixed effect between six heavy metals and SUI. TC partially mediated the relationship of Pb, MeHg, and total Hg with SUI, and LDL-C partially mediated the association of Pb with SUI (all P for mediation < 0.05). Conclusions: Blood heavy metal concentrations influence the development of female SUI, with blood cholesterol mediating the association between different heavy metals and SUI.